Pengelolaan Rantai Pasok dan Daya Saing Kelapa Sawit di Aceh - Fajri Jakfar; Romano Romano; Nurcholis Nurcholis (AGRARIS: Journal of Agribusiness and Rural Development Research, 2015)
Nowadays, supply chain management is vital for palm oil plantations, along with the increases of competitive efforts and equal partnership position between suppliers and processors. The research aimed at mapping supply chain patterns of palm oil plantation, at analyzing performances of palm oil stakeholders, and at analyzing factors influencing performances of stakeholders in the province. The research was conducted using survey method by interviewing and focus group discussion. The results showed that (1) there were 3 supply chains flows from bunches of palm fruit to plants of palm fruit processing; (2) roles of stakeholders in supply chain management determining supply volumes, profits, and value added; and (3) factors influencing performances of stakeholders and competitive advantages were plantation productivity, cost allocation for invesment and operation, capacity  of processing plants, and CPO rendemen rate.